2008
DOI: 10.2967/jnumed.107.045385
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Standardized 18F-FDG PET Diagnosis of Mild Cognitive Impairment, Alzheimer's Disease, and Other Dementias

Abstract: This multicenter study examined 18 F-FDG PET measures in the differential diagnosis of Alzheimer's disease (AD), frontotemporal dementia (FTD), and dementia with Lewy bodies (DLB) from normal aging and from each other and the relation of disease-specific patterns to mild cognitive impairment (MCI). Methods: We examined the 18 F-FDG PET scans of 548 subjects, including 110 healthy elderly individuals (''normals'' or NLs), 114 MCI, 199 AD, 98 FTD, and 27 DLB patients, collected at 7 participating centers. Indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
495
1
23

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 672 publications
(546 citation statements)
references
References 31 publications
27
495
1
23
Order By: Relevance
“…Recent years have witnessed a substantial increase of the applications of nuclear imaging techniques, especially positron emission tomography (PET), in different fields of neurology, like neurodegenerative diseases (Brooks, 2008;Mosconi et al, 2008), epileptic disorders (Lee et al, 2009), and brain cancer (Chen and Silverman, 2008). Recently, quantitative PET imaging has been used as a metabolic biomarker to monitor disease progression and to assess the potentially protective effects of drugs (Schmidt et al, 2008;Whone et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed a substantial increase of the applications of nuclear imaging techniques, especially positron emission tomography (PET), in different fields of neurology, like neurodegenerative diseases (Brooks, 2008;Mosconi et al, 2008), epileptic disorders (Lee et al, 2009), and brain cancer (Chen and Silverman, 2008). Recently, quantitative PET imaging has been used as a metabolic biomarker to monitor disease progression and to assess the potentially protective effects of drugs (Schmidt et al, 2008;Whone et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51] Fluorodeoxyglucose positron emission tomography (FDG-PET) demonstrates decreased occipital glucose metabolism, which is helpful in distinguishing among other neurodegenerative diseases, with one study showing 71% decrease in occipital metabolism without much asymmetry. 52 Other studies found temporo-parieto-occipital cortical hypometabolism as well as hypometabolism within the basal ganglia and pulvinar of the thalami. 53-55 99mTc-hexyamethylpropyleneamine oxime (99mTc-HMPAO) single-photon emission computed tomography (SPECT) imaging shows decreased uptake in the striatum in DLB patients compared with AD patients, but does not distinguish well among the other atypical parkinsonian disorders.…”
Section: Studiesmentioning
confidence: 95%
“…12,15 Esse padrão de hipometabolismo predominantemente frontal facilita o diagnóstico diferencial entre a DA e a DLFT, embora com algum grau de sobreposição, visto que as regiões frontais podem ser igualmente afetadas na DA, assim como o comprometimento do córtex temporoparietal associativo pode ocorrer na DLFT. 16,17 Na Doença de Parkinson também a taxa metabólica cerebral da glicose pode auxiliar no diagnóstico diferencial. Foi observado hipometabolismo no estriado na síndrome parkinsoniana atípica, enquanto que na DP a taxa metabólica está normal ou elevada.…”
Section: Editorialunclassified